Dietary Effect of Red Paprika Used to Enhance the Coloration of Red Tilapia (Oreochromis niloticus) - M. H. Amiruddin; M. F. Norhalis; Sri Sumarwati; Y. Norma-Rashid (Journal of Aquaculture and Fish Health, 2021)
Red tilapia (Oreochromis niloticus) is one of the famous fish cultures in the aquaculture industry, especially in Malaysia. The appearance of redness makes the fish more attractive for customers to buy. Product appearance is one of the big criteria that customers choose when they buy food. Bright color effects give high expectations for high quality, nutritious, and healthy food. Therefore, to achieve quality products it is necessary to research how to improve the color quality of tilapia as desired by customers. The purpose of this study was to identify the dietary effect of red paprika used to enhance the coloration of red tilapia. This study is an experimental quantitative study. Red tilapia used as an experimental material was obtained from Freshwater Hatchery, University Malaysia Terengganu. A descriptive analysis was used to analyze the data in this study. This study shows that giving red paprika has an effect on the length and weight of red tilapia, where the highest length and weight gained (1.79 cm and 12.37 g) given red paprika 2% and the lowest length and weight gained (0.63 cm and 2.5 g) which given 4% red paprika. The findings of this study found that only 2% of red paprika treatment showed different growth performance. The crude protein, lipid, and moisture composition of tilapia were also higher at 2% red paprika treatment. Meanwhile, the highest composition of ash is feed with 4% red paprika content. The result of this research showed that the caudal and dorsal either muscle or fin showed the highest color at the fish which fed with 8% red paprika. The finding also found that 8% red paprika containing diet feed for six weeks could improve the coloration of the red tilapia. Future studies suggest the use of Dunaliella salina microalgae which is one of the richest sources of carotenoids used as dyes in food.